Valid publication of the name Anaphalis hymenolepis (Asteraceae) - Yu, Wen-Bin (Phytotaxa, 2013)
Anaphalis Candolle (1838: 271), with approximately 110 species, is mainly distributed in tropical and subtropical Asia, but a few species occur also in temperate Asia, Europe, and North America. There are 54 species in China, of which 40 species are endemic (Zhu & Bayer 2011). During checking names validly published in the catalogues of Jin & Chen (1994, 1999, 2007; see Yu et al. 2011), we found that the currently accepted name Anaphalis hymenolepis Y.Ling was not validly published (Chen et al. 1966: 99), because two gatherings, K.T. Fu 1051 (male) and T.P. Wang 5506 (female), were simultaneously indicated as types in the protologue contrary to Articles 40.1 and 40.2 of International Code of Nomenclature for algae, fungi, and plants (McNeill et al. 2012). Subsequently, Li (2009: 114) discovered that the name A. hymenolepis was not validly published with two gatherings cited as types; however, he failed to validate this name, because he termed the gathering K. T. Fu 1051 as “Lectotype” contrary to Article 40.6.